The role of oral methotrexate as a steroid sparing agent in refractory eosinophilic asthma. (February 2018) - Bilocca, David; Hargadon, B; Pavord, ID; Green, RH; Brightling, CE; Bradding, P; Wardlaw, AJ; Martin, N; Murphy, AC; Siddiqui, S
The use of oral methotrexate for refractory eosinophilic asthma in a tertiary asthma referral centre, Glenfield Hospital, Leicester, was evaluated between January 2006 and December 2014. The patients ( n = 61) were carefully phenotyped at baseline with markers of airway inflammation. In addition, a structured oral methotrexate proforma was utilized to evaluate response to therapy and adverse events. Oral steroid withdrawal was attempted 3 months after commencing treatment. Several outcomes were evaluated at 12 months, including both efficacy and adverse effects; 15% ( n = 9/61) responded by achieving a decrease in daily oral corticosteroid dose (mean 8.43 (±8.76) mg), although we were unable to identify factors that predicted a treatment response. There were no other significant changes in any other clinical outcome measures. There was a high rate of adverse events (19/61 (31%)), primarily gastrointestinal/hepatitis. Our findings support the use of biological agents in preference to using oral methotrexate as a steroid sparing agent at the first instance. In the event of failure of these agents, oral methotrexate remains a therapeutic option, which can be considered in highly specialist severe asthma centres.